2017
DOI: 10.1787/9789264279285-en
|View full text |Cite
|
Sign up to set email alerts
|

Guidance Document on the Reporting of Defined Approaches and Individual Information Sources to be Used within Integrated Approaches to Testing and Assessment (IATA) for Skin Sensitisation

Abstract: This publication was developed in the IOMC context. The contents do not necessarily reflect the views or stated policies of individual IOMC Participating Organisations. The Inter-Organisation Programme for the Sound Management of Chemicals (IOMC) was established in 1995 following recommendations made by the 1992 UN Conference on Environment and Development to strengthen co-operation and increase international co-ordination in the field of chemical safety. The Participating Organisations are FAO, ILO, UNDP, UNE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 54 publications
(87 reference statements)
0
7
0
Order By: Relevance
“…Since the first publication of the adverse outcome pathway for skin sensitization in vitro in 2012 (OECD, 2012), efforts have been made to develop an Integrated Approach to Testing and Assessment (IATA) for skin sensitization. This approach of toxicity testing, hazard and risk assessment integrates various types of chemical and toxicological data into the decision-making process (OECD, 2014;OECD, 2017).…”
Section: Altex Preprint Publishedmentioning
confidence: 99%
See 2 more Smart Citations
“…Since the first publication of the adverse outcome pathway for skin sensitization in vitro in 2012 (OECD, 2012), efforts have been made to develop an Integrated Approach to Testing and Assessment (IATA) for skin sensitization. This approach of toxicity testing, hazard and risk assessment integrates various types of chemical and toxicological data into the decision-making process (OECD, 2014;OECD, 2017).…”
Section: Altex Preprint Publishedmentioning
confidence: 99%
“…Skin sensitization is a comprehensive immune response, therefore, alternative methods that assess a single key event alone are considered insufficient for evaluating the ability of a test substance to induce skin sensitization. Thus, focus has been increasingly laid on complex assessment that combines at least two in chemico or in vitro methods (addressing different key events), resulting in the "2 out of 3 approach" (OECD, 2017;Bauch et al, 2012). A single test may be performed for each of the key events 1, 2 and 3 (peptide/protein binding, keratinocyte activation, and dendritic cell activation), respectively.…”
Section: Altex Preprint Publishedmentioning
confidence: 99%
See 1 more Smart Citation
“…The Jurkat Clone E6-1 human T lymphocyte is an immortal cell line often used in studies on in vitro human T cell activation (Fernández-Riejos et al, 2008;Pan et al, 2015;Ngo et al, 2017;Chen et al, 2018;Vis et al, 2018;Colin-York et al, 2019;Kim et al, 2019). It has been reported that for some chemicals that incubating them in vitro with the Jurkat T cells in culture medium induced early T cell activation manifesting as an increase in CD69 expression on the Jurkat T cells in the absence of APCs in the test system (Fernández-Riejos et al, 2008;Chen et al, 2018;Vis et al, 2018).…”
Section: Test Concentrations and Treatment Of The Cellsmentioning
confidence: 99%
“…(2) The protein-hapten (chemical) complexes may bind the T cell antigen receptors (TCRs) on the Jurkat T cells directly in this in vitro condition without the aid of APCs. (3) Like a naïve T cell, the Jurkat Clone E6-1 human T cell line expresses CD3 and TCRs and is commonly used in in vitro studies on human T cell activation (Fernández-Riejos et al, 2008;Pan et al, 2015;Ngo et al, 2017;Chen et al, 2018;Vis et al, 2018;Colin-York et al, 2019;Kim et al, 2019). ( 4) It ap-model, CD69 expression on the T cells indeed was induced by most of the sensitizers.…”
Section: The Dose-effect Relationship Of Cd69 Expression and Cell Viabilitymentioning
confidence: 99%